1967
DOI: 10.1039/j19670001038
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray, infrared, and magnetic studies of α- and β-ruthenium trichloride

Abstract: Physical measurements have been made on samples of u-and P-RuCI, of relatively high purity. From X-ray powder patterns, the existence of a superstructure has been detected in a-RuCI,, and the structure of P-RuCI, has been found to be of the P-TiCI, type with linear chains of ruthenium atoms lying in distorted octahedra of chlorine atoms. The infrared spectra have been obtained down to 70 cm.-l; the nine bands observed for P-RuCI, indicate that the space group is the trigonal P3cl (C3,"), which means that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
104
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 0 publications
12
104
0
1
Order By: Relevance
“…Early reports assigned the trigonal space group P3 1 12 [82] (known as the CrCl 3 structure type, although it has been shown that CrCl 3 does not actually adopt it) and the AlCl 3 type [85], and a tendency to form stacking defects has been noted [86]. The Ti 3 O type was also reported [81]. More recently an X-ray and neutron diffraction study reported the monoclinic AlCl 3 structure for small single crystals at and below room temperature, and a phase transition in large single crystals from a trigonal structure at room temperature to the monoclinic AlCl 3 structure type below about 155 K [80].…”
Section: Compoundmentioning
confidence: 99%
“…Early reports assigned the trigonal space group P3 1 12 [82] (known as the CrCl 3 structure type, although it has been shown that CrCl 3 does not actually adopt it) and the AlCl 3 type [85], and a tendency to form stacking defects has been noted [86]. The Ti 3 O type was also reported [81]. More recently an X-ray and neutron diffraction study reported the monoclinic AlCl 3 structure for small single crystals at and below room temperature, and a phase transition in large single crystals from a trigonal structure at room temperature to the monoclinic AlCl 3 structure type below about 155 K [80].…”
Section: Compoundmentioning
confidence: 99%
“…Depending on the method of preparation two structurally different forms are obtained (12). A black a-form has Ruit in a significantly distorted octahedron (19) resulting in paramagnetism with Curie-Weiss law behavior between 300 and 80 K (10) and a more complicated magnetic behavior at lower temperatures (19). The dark brown @-form is antiferromagnetic below-600 K on account of rather short Ru-Ru bonds (2.83 A) (19); however, the presence of a-RuC1, as contaminant has obscurred the situation somewhat.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…We have found that, structures with C2/m 22 and Cmc2 1 space group symmetries are most favorable with almost degenerate energies. Previously suggested P 3 1 12 structure 3,21 yields total energy comparable to those of C2/m and Cmc2 1 structures with the energy difference smaller than 0.4 meV per formula unit (f.u.). Energy differences between different interlayer magnetic orders are smaller than 0.1 meV / f.u., and magnitude of interlayer exchange interactions estimated from interlayer hopping integrals are smaller than 0.05 meV.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, α-RuCl 3 has a three-dimensional crystal structure consisting of RuCl 3 layer stacking, and interlayer coupling and interaction terms can introduce another complication. Experimentally, both P 3 1 12 and C2/m space groups have been suggested as the crystalline symmetry in this compound 3,6,11,21,22 . As an illustrative example, Fig.…”
Section: Introductionmentioning
confidence: 99%